Laser produced electromagnetic pulses: generation, detection and mitigation. (2020) - Consoli, Fabrizio; Tikhonchuk, Vladimir T.; Bardon, Matthieu; Bradford, Philip; Carroll, David C.; Cikhardt, Jakub; Cipriani, Mattia; Clarke, Robert J.; Cowan, Thomas E.; Danson, Colin N.; De Angelis, Riccardo; De Marco, Massimo; et al.
Abstract : This paper provides an up-to-date review of the problems related to the generation, detection and mitigation of strong electromagnetic pulses created in the interaction of high-power, high-energy laser pulses with different types of solid targets. It includes new experimental data obtained independently at several international laboratories. The mechanisms of electromagnetic field generation are analyzed and considered as a function of the intensity and the spectral range of emissions they produce. The major emphasis is put on the GHz frequency domain, which is the most damaging for electronics and may have important applications. The physics of electromagnetic emissions in other spectral domains, in particular THz and MHz, is also discussed. The theoretical models and numerical simulations are compared with the results of experimental measurements, with special attention to the methodology of measurements and complementary diagnostics. Understanding the underlying physical processes is the basis for developing techniques to mitigate the electromagnetic threat and to harness electromagnetic emissions, which may have promising applications.